Spirometric Outcomes Following Lobectomy: A Non-Tuberculosis Perspective (Faridpur Medical College Journal, 2025)
Lobectomy offers significant symptom relief and high sputum culture conversion rates in diverse pulmonary conditions. The procedure impacts lung function. Spirometry serves as a critical tool for evaluating these changes and guiding postoperative recovery. This study aims to analyze spirometric outcomes of lobectomy in non-tubercular diseases. This pretest-posttest design study evaluated spirometric outcomes of lobectomy in 30 patients with non-tuberculous pulmonary diseases at National Institute of Diseases of the Chest and Hospital (NIDCH) from January 2022 to June 2023. Pre- and postoperative lung function was analyzed using FEV1, FVC, and FEV1/FVC ratio. The study included 30 patients, with a mean age of 35.6 years (±16.1 SD), comprising 21 males and 9 females. Smoking history was found in 9 patients (30%), while 21 (70%) were non-smokers. The most common diagnoses were bronchiectasis (13 cases) and adenoma (6 cases), with lesions predominantly in the upper lobes (13 cases). Spirometric analysis showed a slight decrease in mean FEV1 (from 1.9 ± 0.5 L to 1.7 ± 0.7 L) and FVC (from 2.4 ± 0.5 L to 2.2 ± 0.5 L) postoperatively, but these changes were not statistically significant (p > 0.05). The FEV1/FVC ratio (73.7±22.3 to 76.6±14.3) showed a modest increase, suggesting preserved airflow despite slight lung volume reductions. This study shows that lobectomy for non-tuberculous conditions leads to minimal, statistically non-significant changes in spirometric outcomes, with preserved lung function postoperatively. These findings support lobectomy as a safe and effective option for managing non-tuberculous pulmonary conditions.Faridpur Med. Coll. J. 2025;20(2):13-17